Timing of glaucoma treatment in patients with MICOF: A retrospective clinical study - Li, Zhao; Wang, Qun; Zhang, Shi-Feng; Huang, Yi-Fei; Wang, Li-Qiang (Frontiers in Medicine, 2022)
Purpose: To summarize and discuss the treatment and timing of glaucoma in patients with MICOF keratoprosthesis implantation to guide follow-up clinical treatment. Methods: The data of 39 eyes (39 patients) with MICOF keratoprosthesis implantation in our hospital from January 1, 2002 to December 31, 2017 were collected, including patients with preexisting glaucoma and those who developed glaucoma de novo after MICOF. The sex, age, preoperative diagnosis, glaucoma surgery, keratoplasty, times of keratoplasty, best-corrected visual acuity (BCVA) and final follow-up corrected visual acuity, visual field (VF) defect and cup-to-disk ratio (CDR) were statistically analyzed. Results: Among 16 eyes with preexisting glaucoma, 8 eyes underwent glaucoma surgery before MICOF, 4 eyes underwent glaucoma surgery combined with MICOF and 4 eyes were managed medically. Among 23 eyes with de novo glaucoma, 7 eyes were treated with surgery and 16 eyes were treated with medication only. 9 (56.3%) had corneal transplants with preexisting glaucoma, which was a higher percentage than that in the patients with de novo glaucoma (n=5, 21.7%, P=0.043). In both the preexisting glaucoma group and the de novo glaucoma group, most common causes were alkali burns (56.3% of preexisting glaucoma and 43.5% of de novo glaucoma). There was no significant difference between the operation and initial visual acuity, postoperative visual acuity, BCVA, CDR or VF defect. In the de novo glaucoma group, the final follow-up visual acuity of the glaucoma surgery group (1.56±1.07) was worse than that of the mediation group (0.44 ±0.53) (P<0.017). Among the complications, the incidence of cornea melting in the patients treated with medications only (n=10) was significantly higher than that in the patients treated with glaucoma surgery (n=0, P=0.007), but there was no significant difference in the other complications. Conclusion: Among patients with MICOF, those who have undergone keratoplasty are more likely to develop glaucoma before surgery and glaucoma needs to be prevented. Surgical treatment can be selected according to the ocular surface condition in the patients with de novo glaucoma to reduce the occurrence of complications.